(untitled) (Ibrahim Cardiac Medical Journal, 2025)
Background & objective: Dengue fever, an endemic mosquito-borne viral disease, poses a significant health challenge globally, especially in tropical regions like Bangladesh. The country has witnessed an alarming rise in dengue-related mortality, particularly since 2021, culminating in a record high in 2023, necessitating an investigation into the determinants of dengue mortality to improve patient outcomes. This study aims to identify demographic, clinical, and biochemical factors associated with mortality in patients diagnosed with dengue fever in a tertiary care hospital in Dhaka City. Methods: This case-control study was conducted at Aalok Hospital in Mirpur, Dhaka, focusing on patients aged 18 years and older who were admitted during the dengue outbreak of 2024. The study included 123 participants, comprising 7 cases (patients who died from dengue) and 116 controls (patients who survived) of the disease. Inclusion criteria required a confirmed diagnosis of dengue fever or dengue hemorrhagic fever based on clinical and laboratory findings, including positive dengue NS1 antigen or IgM antibodies. Patients with severe comorbidities and those with a recent history of dengue infection were excluded to avoid bias. Data were collected on demographic, socioeconomic, clinical, and biochemical factors, suspected to be associated with the death (the outcome variable) of dengue patients. All the suspected exposure variables were then compared between case and control groups to see whether they were associated with the outcome fo interest. Result: The study found that the mean age of the cases was significantly higher than that of the controls. A notable proportion of both groups belonged to middle- and upper-middle-class families, with no significant difference in socioeconomic status. However, service-holders carried a higher mortality risk compared to other occupants. Clinical symptoms such as hypotension, retro-orbital pain, and restlessness were significantly more common among the case group. Furthermore, the cases demonstrated a higher incidence of altered sensorium, ascites, and electrolyte imbalances. Notably, 57% of the cases exhibited acute liver injury (ALT > 200 U/L), compared to only 11.2% of the controls. Thrombocytopenia and gastrointestinal bleeding manifestations were more prevalent in the case group. Additionally, complications like shock syndrome and disseminated intravascular coagulation (DIC) were significantly associated with mortality. Conclusion: Addressing the multifaceted determinants of dengue mortality is crucial for improving patient outcomes and reducing the burden of this disease in Bangladesh. A comprehensive, concerted clinical management, is essential to combat the rising dengue incidence and the mortality caused by it. Ibrahim Card Med J 2024; 14(1): 40-45